Evaluation of postural balance in postmenopausal women and its relationship with bone mineral density- a cross sectional study - Cangussu, Luciana Mendes [UNESP]; Nahas-Neto, Jorge [UNESP]; Nahás, Eliana Aguiar Petri [UNESP]; Cesar Rodrigues Barral, Ana Beatriz [UNESP]; Buttros, Davi de Araujo [UNESP]; Uemura, Gilberto [UNESP] (Biomed Central Ltd., 2012)
Background: Low bone mineral density (BMD) and falls are common problems encountered in the postmenopausal women. The purpose was to evaluate the association between postural balance and BMD in postmenopausal women and its relation to risk for falls.Methods: In this cross-sectional study, 225 women in amenorrhea > 12 months and age >= 45 years were included and divided, according to BMD, in T-score values > -2.0 SD (n = 140) and <= -2 SD (n = 85). Those with neurological or musculoskeletal disorders, history of vestibulopathies, uncorrected visual deficit or drug use that could affect balance were excluded. History of falls (last 24 months), clinical and anthropometric characteristics were evaluated. Postural balance was assessed by stabilometry (force platform). For statistical analysis were used Wilcoxon's Test, Chi-Square Test and logistic regression method for fall risk (Odds Ratio-OR).Results: Patients with BMD > -2.0 SD were younger, with shorter time since menopause, and showed higher BMI as compared to those with low BMD (<= -2 SD) (p < 0.05). It was observed that 57.8% of the participants reported fall episodes without significant difference distribution between the groups (p = 0.055). No differences were found from the comparison between the groups (p > 0.05) for stabilometric parameters. Risk for falls increased with age (OR 1.07; CI 95% 1.01-1.13), current smoking (OR 2.19; CI 95% 1.22-3.21) and corrected visual deficit (OR 9.06; CI 95% 1.14-4.09). In contrast, hormone therapy (HT) use was significantly associated with reduced risk for falls (OR 0.48; CI 95% 0.26-0.88).Conclusions: In postmenopausal women, BMD did not show association with postural balance or risk for falls. Age, smoking and corrected visual deficit were clinical indicators of risk for falls whereas HT use showed to be a protective factor.
Keywords: Menopause; Postural Balance; Bone Mineral Density; Falls